Cytotaxonomic diagnoses of two Neotropical swift species: Streptoprocne biscutata and Streptoprocne zonaris (Aves: Apodidae) - Ribeiro, Juliano; Torres, Rodrigo A.; Adam, Mônica L.; Cornélio, Débora A. (Zootaxa, 2003)
Specimens of Streptoprocne biscutata and Streptoprocne zonaris were studied cytogenetically in order to identify the features of their karyotypes and to increase our knowledge of the karyotypical constitutions of family Apopidae in the Neotropical region. Analysis of Streptoprocne biscutata revealed 2n= 64 (22 macrochromosmes + 42 microchromosomes) whereas Streptoprocne zonaris is characterized by 2n= 66 (18 macrochromosmes + 48 microchromosomes). It was not possible to recognize chromosomes related to sex determination in either species. We make available chromosome data that will prove useful to a global biological characterization of Apodidae, contributing to a reconnaissance of study of avian diversity in the Neotropics.